2021
DOI: 10.1016/j.adro.2021.100803
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Timing Between Androgen Deprivation Therapy and External Beam Radiation Therapy in Patients With Localized, High-Risk Prostate Cancer

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A recent large individual patient data meta-analysis by Kishan et al, mainly including HR and IR PCa, reported no benefit in MFS when prolonging NAHT from 3–4 months to 6–9 months [ 56 ]. On the other hand, an NCDB study including 37,606 patients with HR PCa treated with RT plus ADT found improved OS when NAHT was given for 8–11 weeks compared to shorter courses (HR 0.9), but not when extending it beyond 11 weeks [ 57 ]. These results suggest that if an underlying benefit to neoadjuvant ADT exists, it could be marred by a delay of over 3 months of the definitive ablative treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent large individual patient data meta-analysis by Kishan et al, mainly including HR and IR PCa, reported no benefit in MFS when prolonging NAHT from 3–4 months to 6–9 months [ 56 ]. On the other hand, an NCDB study including 37,606 patients with HR PCa treated with RT plus ADT found improved OS when NAHT was given for 8–11 weeks compared to shorter courses (HR 0.9), but not when extending it beyond 11 weeks [ 57 ]. These results suggest that if an underlying benefit to neoadjuvant ADT exists, it could be marred by a delay of over 3 months of the definitive ablative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the exclusion of patients receiving pelvic RT and long-term ADT in Spratt’s meta-analysis precludes extrapolating their results to HR PCa. This may warrant further study given the intriguing results seen in the NCDB studies using the NAHT approach [ 50 , 57 ]. Moreover, the recently presented SANDSTORM study showed that in patients receiving WPRT, C-AHT was associated with higher rates of distant metastases and the authors support that NA-CHT should be preferred when pelvic RT is indicated [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that 6-month NADT combined with RT is an effective treatment for patients with locally advanced PCa, particularly in men without pre-existing metabolic or nodal metastatic comorbidities that could be exacerbated by extended ADT [62]. Another study also showed that NADT initiation 8 to 11 weeks before RT is associated with significantly improved OS compared with shorter NADT duration in high or very high-risk PCa patients [63]. Contrarily, a recent meta-analysis reported that NADT extension from 3-4 months to 6-9 months in patients with localized PCa receiving RT does not improve MFS, indicating that the magnitude of the benefit could vary [64].…”
Section: Rt + Nadt Vs Rt Alonementioning
confidence: 98%